A Wearable In-Ear Encephalography Sensor for Monitoring Sleep: Preliminary Observations from Nap Studies - Looney,D; Goverdovsky,V; Rosenzweig,I; Morrell,MJ; Mandic,DP (Annals of the American Thoracic Society, 2016)
RATIONALE: To date the only quantifiable measure of neural changes that define sleep is electroencephalography (EEG). Although widely used for clinical testing, scalp-electrode EEG is costly and poorly tolerated by sleeping patients. OBJECTIVES: This is a pilot study to assess the agreement between EEG recordings obtained from a new ear-EEG sensor and those obtained simultaneously from standard scalp electrodes. METHODS: Participants were 4 healthy men, ages 25 to 36 years. During naps, EEG tracings were recorded simultaneously from the ear sensor and standard scalp electrodes. A clinical expert, blinded to the data collection, analyzed 30-second epochs of recordings from both devices using standardized criteria. The agreement between scalp- and ear-recordings was assessed. MEASUREMENTS AND MAIN RESULTS: We scored 360 epochs (scalp-EEG and ear-EEG) of which 254 (70.6%) were scored as non-rapid-eye movement (NREM) sleep using scalp-EEG. The ear-EEG sensor had a sensitivity of 0.88 (95% CI 0.82 to 0.92) and specificity of 0.78 (95% CI 0.70 to 0.84) in detecting N2/N3 sleep. The kappa coefficient, between the scalp- and ear-EEG, was 0.65 (95% CI 0.58 to 0.73). As a sleep monitor (all NREM sleep stages versus wake), the in-ear sensor had a sensitivity of 0.91 (95% CI 0.87 to 0.94) and specificity of 0.66 (95% CI 0.56 to 0.75). The kappa coefficient was 0.60 (95% CI 0.50 to 0.69). CONCLUSIONS: Substantial agreement was observed between recordings derived from a new ear-EEG sensor and conventional scalp electrodes on 4 healthy volunteers during daytime naps.